Evaluation of the protective properties and genotoxic potential of pyrazolo pyridine derivatives against neutron and gamma radiation using the Ames/Salmonella test system - Aygun, Buenyamin; Alaylar, Burak; Turhan, Kadir; Karadayi, Mehmet; Cinan, Esra; Turgut, Zuhal; Sezer, Tansu; Sola, Vedat; Koc, Taha Yasin; Karabulut, Abdulhalik (TAYLOR & FRANCIS LTD, 2024)
Purpose: Nuclear applications are being increasingly used in various fields, necessitating studies to protect from radiation hazards and their effects. In this study, five different chemical structures of pyrazolo [3,4-b] pyridine derivatives were synthesized. The gamma and neutron radiation protective abilities of these samples were determined and demonstrated their potential use as ingredients in radioprotective drugs. Material and methods: Gamma radiation absorption parameters were calculated both theoretical and experimental. Important attenuation parameters for fast neutrons (4.5 MeV energy radiation) were figured out using the Monte Carlo simulation Geant4 code. Additionally, experimental dose rates were measured for each sample and compared to those of Paraffin and high-density polyethylene, an organic substance. Besides, Ames/Salmonella test system was aimed to detecting genotoxicity features of pyrazolo pyridine derivatives. Results: All results demonstrated that each sample possesses both gamma and neutron radiation attenuation capabilities. It was determined that sample PPC4 (C20H14BrN5) exhibited the highest gamma radiation attenuation capacity among all samples, while sample PPC2 (C22H20N6) displayed an excellent neutron stopping capacity. The genotoxic properties of pyrazolo[3,4-b] pyridine derivatives were examined using the Ames/Salmonella test, and as a result, it was determined that these substances did not exhibit genotoxic effects at test doses up to 5 mM. Conclusion: All obtained results indicate that all PPC (pyrazolo[3,4-b] pyridine derivatives) samples do not possess a toxic effect, and they can be utilized as an active substance for the development of a drug or cream with protective properties against both gamma and neutron radiations.
Keywords: Genotoxicity; pyrazolopyridine; radiation; radioprotector; NITRO-N-NITROSOGUANIDINE; AMINOKETONES; RAY; Life Sciences & Biomedicine - Other Topics; Nuclear Science & Technology; Radiology, Nuclear Medicine & Medical Imaging